China and the West Music, Representation, and Reception - Yang, Hon-Lu; Saffle, Michael; Yang, Hon-Lun; Michigan Publishing (University of Michigan) (University of Michigan Press, 2017)
China and the West: Music, Representation, and Reception is the first book to explore how Chinese and Western musical materials and traditions-those involving instruments, melodies, rhythms, staged diversions (including operas and musical comedies), concert works, film scores, and digital recordings of several kinds-have gradually moved closer together and become increasingly accepted, as well as exploited, in Asia as well as Europe and North America. Although aimed in large part at a scholarly audience, China and the West should appeal to general readers of many kinds: those interested in politics, cultural history and theory, gender studies, sociology, theater, and media studies as well as musical composition and performance of 'classical' as well as traditional and popular kinds.
Keywords: Orientalism in music; Exoticism in music; Music : China : Western influences; Music : Chinese influences; Music; China